The Planning of Islamic Educational Media to Improve Young Children's Understanding of the Concept of Tawheed at Tadika Al-Fikh Orchard - Setiawan, Hasrian Rudi; Maysarah, Maysarah (Yayasan Rahmat Islamiyah, 2025)
This study aims to explore the planning of Islamic educational media to improve young children's understanding of the concept of Tawheed at Tadika Al-Fikh Orchard. Employing a qualitative case study approach, data were collected through interviews, observations, and document analysis. The findings revealed that teachers and curriculum planners adopted a collaborative, thematic, and developmentally appropriate approach to media selection and usage. Media such as nasheeds, illustrated storybooks, and visual aids were intentionally planned to simplify the abstract concept of Tawheed for early childhood learners. The study also highlights the role of parental involvement, repetition, and the alignment of content with children's daily experiences. Overall, the research confirms that well-planned Islamic educational media significantly enhance children’s comprehension and internalization of core Islamic beliefs, particularly the oneness of Allah (Tawheed).